Plant leaf imitating hydrogel composite material and preparation method thereof

By preparing a plant leaf hydrogel composite based on PVA and strong hygroscopic monomer, the problems of unstable moisture absorption and poor simulation effects of existing hygroscopic salt materials are solved, and stable simulation and good durability of the "water absorption valley" of plant leaves are achieved.

CN119529317AActive Publication Date: 2025-02-28JIANGNAN UNIV

Patent Information

Application Number
CN202411502948.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing self-driven water-absorbing imitation plant leaf materials that use hygroscopic salts are prone to hygroscopic salts during application, resulting in unstable moisture absorption, poor simulation effect, poor durability, and complex material structure and poor internal bond fastness.

Method used

By preparing a plant leaf hydrogel composite material, the material uses the biomaterial polyvinyl alcohol (PVA) as the substrate, and blends the hydrogel prepolymer solution with strong hygroscopic monomer, crosslinking agent and initiator, and copolymerizes with green fabric to form a hydrogel composite material, avoiding the use of hygroscopic salts.

Benefits of technology

The stable simulation of the "water absorption valley" of plant leaves is achieved, with good durability and binding fastness, avoiding the problem of hygroscopic salt leakage, and the structure is simple and the preparation process is simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529317A_ABST
    Figure CN119529317A_ABST
Patent Text Reader

Abstract

The invention discloses a plant leaf imitating hydrogel composite material and a preparation method thereof, and belongs to the field of bionic composite materials. The preparation method comprises the following steps: firstly, preparing printing paste by compounding a coloring agent, printing a fabric to obtain a green fabric capable of simulating spectral characteristics of green peaks and red edges of plant leaves, and simulating fence tissues and skeletons in a leaf structure by using the green fabric; then taking a biological material polyvinyl alcohol (PVA) as a base material, adding a monomer with strong hygroscopicity, a cross-linking agent and an initiator, and blending to prepare a hydrogel prepolymer solution; and finally, pouring the hydrogel prepolymer solution into a mold containing the green fabric for copolymerizing, so that hydrogel is directly formed on the surface of the fabric and in pores, and the plant leaf imitating hydrogel composite material is obtained. The material gets rid of dependence on moisture absorption salt, and has the advantages of stable water absorption and simulation effects, good durability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a plant leaf imitation hydrogel composite material and a preparation method thereof, and belongs to the field of bionic composite materials. Background Art

[0002] Plant leaves are an important part of plants. Due to their diverse functional structures and survival functions, they have become one of the typical bionic prototypes. At present, bionic structures and materials inspired by plant leaves have been widely used in materials science, medicine, sensors, mechanics, optics and other fields. Among them, bionic materials that simulate the spectral characteristics of plant leaves can counteract hyperspectral remote sensing detection technology, improve the survivability and combat effectiveness of targets in the plant background, and play an important role in the field of national defense and security. Although there are many types of plant leaves, their reflectance spectra have four significant spectral characteristics in the range of 400-2500nm: "green peak", "red edge", "near infrared plateau" and "water absorption valley".

[0003] At present, the three spectral characteristics of plant leaves, namely "green peak", "red edge" and "near infrared plateau", can be effectively simulated by using colorant compounding and material structure regulation. However, the simulation effect of "water absorption valley" is still not ideal. The formation of the spectral characteristics of "water absorption valley" is mainly related to the water in plant leaves. In existing research, there are three main ways to give materials "water absorption valley", namely mechanical water addition, internal encapsulation of water and self-driven water absorption. Among them, self-driven water-absorbing materials can adjust their own water content according to the ambient humidity, simulate the transpiration of plant leaves and become a major research hotspot. However, existing self-driven water-absorbing plant leaf imitation materials, such as CN114214847A, usually use hygroscopic metal salts with high hygroscopicity to absorb moisture in the air so that the material can simulate the "water absorption valley", but in the application process, the hygroscopic salt in the material is prone to leakage, resulting in unstable water absorption, poor simulation effect, and poor durability. At the same time, the material structure is complex and the internal bonding strength is poor. Summary of the invention

[0004] [Technical issues]

[0005] The existing self-driven water-absorbing plant leaf-like materials using hygroscopic salt are prone to hygroscopic salt dew during application, resulting in unstable water absorption, poor simulation effect of "water absorption valley", and poor durability. At the same time, the material structure is complex and the internal bonding strength is poor.

[0006] [Technical solution]

[0007] In order to solve the above problems, the present invention provides a plant leaf imitation hydrogel composite material and a preparation method thereof, which is free from dependence on hygroscopic salts and has the advantages of stable water absorption and simulation effects, good durability, etc. The present invention first prepares a printing paste by compounding a colorant, and prints the fabric to obtain a green fabric that can simulate the "green peak" and "red edge" spectral characteristics of plant leaves, and simulates the palisade tissue and skeleton in the leaf structure with the green fabric; then, the biomaterial polyvinyl alcohol (PVA) is used as a substrate, and a monomer with strong hygroscopicity, a cross-linking agent, and an initiator are added to prepare a hydrogel prepolymer solution; finally, the hydrogel prepolymer solution is poured into a mold containing green fabric for copolymerization, so that a hydrogel is directly formed on the surface of the fabric and inside the pores, and a plant leaf imitation hydrogel composite material is obtained. The biomimetic composite material obtained by the present invention has all the spectral characteristics of plant leaves at 400-2500nm, and is similar to the structural characteristics of plant leaves. At the same time, the hydrogel with strong hygroscopicity in the composite material can self-drive water absorption / release according to the ambient humidity, realize the simulation of the transpiration of plant leaves, and avoid the problem of hygroscopic salt leakage. In addition, the hydrogel has strong adhesion based on strong hydrogen bonding and has excellent bonding strength with its internal fabric.

[0008] The first object of the present invention is to provide a method for preparing a plant leaf imitation hydrogel composite material, comprising the following steps:

[0009] (1) Preparation of green fabrics:

[0010] The colorant, printing auxiliary agent and water are mixed evenly and stirred into a slurry to obtain a green printing paste; then the printing paste is printed on the surface of the fabric by a screen printing method to obtain a green fabric;

[0011] (2) Preparation of hydrogel prepolymer solution:

[0012] PVA, a strong hygroscopic monomer, a cross-linking agent, an initiator, and water are mixed and stirred uniformly to obtain a hydrogel prepolymer solution;

[0013] (3) Preparation of plant leaf-like hydrogel composites:

[0014] The green fabric obtained in step (1) is mixed with the hydrogel prepolymer solution obtained in step (2), and the mixture is polymerized by heating to obtain a plant leaf imitating hydrogel composite material.

[0015] In one embodiment of the present invention, the colorant in step (1) includes one or more of chromium oxide, disperse dyes, vat dyes, acid dyes, reactive dyes, dry leaf powder, and sodium copper chlorophyll.

[0016] In one embodiment of the present invention, the printing auxiliary agent in step (1) includes one or more of a dispersant, a thickener, and a binder.

[0017] In one embodiment of the present invention, the dispersant includes one or more of 85A, AD-4600, 5080W, NNO, DM 1501, DM1501N, PVP, and BYK-190.

[0018] In one embodiment of the present invention, the thickener includes one or more of TF-3181SS, TF-313E, TF-313B, TF-312NW, DM-5221G, DM-5228, DM-5298, and sodium alginate.

[0019] In one embodiment of the present invention, the adhesive includes one or more of TF-3211, TF-321A, TF-3201YD, TF-3201R, TEP, BST-N788, DM 5128A, and DM 5120.

[0020] In one embodiment of the present invention, the green printing paste described in step (1) is prepared by mixing a colorant, a printing auxiliary agent and water and stirring them evenly into a slurry; wherein the amount of the colorant in the green printing paste is 0.1-5.0wt%; the amount of the printing auxiliary agent in the green printing paste is 5-40.0wt%.

[0021] In one embodiment of the present invention, the fabric described in step (1) comprises one or more of polyester fabric, polyester-cotton blended fabric, cotton fabric, viscose fabric, and nylon fabric.

[0022] In one embodiment of the present invention, the PVA described in step (2) includes one or more of polyvinyl alcohol 1788, polyvinyl alcohol 1788 low viscosity, polyvinyl alcohol 1799, polyvinyl alcohol 1792, polyvinyl alcohol 0588, polyvinyl alcohol 0599, polyvinyl alcohol 1750±50, polyvinyl alcohol 124, and polyvinyl alcohol 350.

[0023] In one embodiment of the present invention, the highly hygroscopic monomer described in step (2) includes one or more of acrylic acid, acrylic acid salts, acrylamide, acrylic acid-acrylamide copolymer, N-isopropylacrylamide, 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer, sodium p-styrene sulfonate, lignin, chitosan, cellulose, carboxymethyl cellulose, sodium alginate, and quaternary ammonium salt guar gum.

[0024] In one embodiment of the present invention, the cross-linking agent in step (2) includes one or more of N,N-methylenebisacrylamide, glutaraldehyde, citric acid, and ethylene glycol diacrylate.

[0025] In one embodiment of the present invention, the initiator in step (2) includes one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, epichlorohydrin, and boric acid.

[0026] In one embodiment of the present invention, in step (2), the mass ratio of PVA to the highly hygroscopic monomer in the hydrogel prepolymer solution is (0.4-0.8):1; more preferably 0.6:1.

[0027] In one embodiment of the present invention, in step (2), the mass fraction of PVA in the hydrogel prepolymer solution is 10%-20%.

[0028] In one embodiment of the present invention, in step (2), the mass fraction of the strongly hygroscopic monomer in the hydrogel prepolymer solution is 0-50%, preferably 0-50% and not 0.

[0029] In one embodiment of the present invention, in step (2), the mass fraction of the crosslinking agent in the hydrogel prepolymer solution is 0.1-1.0%.

[0030] In one embodiment of the present invention, in step (2), the mass fraction of the initiator in the hydrogel prepolymer solution is 0.1-1.0%.

[0031] In one embodiment of the present invention, in step (2), PVA is first dissolved in water to prepare a PVA solution, and then the obtained PVA solution is blended with a highly hygroscopic monomer, a cross-linking agent, an initiator, and water and stirred uniformly to obtain a hydrogel prepolymer solution.

[0032] In one embodiment of the present invention, the PVA solution in step (2) is obtained by dissolving PVA in water; wherein the mass fraction of PVA in the PVA solution is 5-50%.

[0033] The second object of the present invention is to provide a plant leaf imitation hydrogel composite material based on the above method.

[0034] The third object of the present invention is to provide application of the above-mentioned plant leaf imitation hydrogel composite material in the field of national defense security.

[0035] [Beneficial Effects]

[0036] The plant leaf-imitating hydrogel composite material prepared by the present invention can simulate the "water absorption valley" of plant leaves, and the spectral correlation coefficient with the real Camellia japonica leaves is as high as 0.98 or more. The bionic composite material prepared by the present invention does not use hygroscopic salts, and can simulate the transpiration of plant leaves only through hydrogels with strong hydrophilicity, avoiding the problem that hygroscopic salts are easy to leak, resulting in unstable water absorption of materials, poor simulation effect, and poor durability. The hydrogel has strong adhesion based on strong hydrogen bonding, and has excellent bonding strength with its internal fabric. The bionic composite material prepared by the present invention has a simple structure, a simple preparation process, and has industrial advantages. The plant leaf-imitating hydrogel composite material prepared by the present invention uses textile materials as a skeleton, and uses biomaterials PVA and hygroscopic monomers as hydrogel substrates, and has good biocompatibility and degradability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the structure of the plant leaf imitating hydrogel composite material of the present invention.

[0038] Figure 2 It is a schematic diagram comparing the spectral curves of the plant leaf imitating hydrogel composite material and the camellia leaf prepared in Example 1 of the present invention and Comparative Example 1. Specific implementation plan

[0039] The outstanding advantages and remarkable features of the present invention are further described below by implementing examples, but the present invention is not limited to the implementing examples.

[0040] The plant leaves in the "imitation plant leaves" involved in the present invention include but are not limited to flowers, Schefflera, Hypericum, cherry blossoms, beech trees, maple poplars, dieffenbachia, ginkgo, peach trees, camellias, magnolias, camphor leaves, etc.

[0041] The present invention relates to the following testing method:

[0042] (1) Reflection spectrum curve

[0043] The sample was placed in the solid reflectance sample test chamber of the Lambda 950 UV-Vis-NIR spectrophotometer, and the reflectance spectrum curve of the sample was tested in the range of 4000-1200nm, with a wavelength interval of 10nm.

[0044] (2) Spectral correlation coefficient (γ)

[0045] The spectral correlation coefficient between the sample and the green plant leaves was calculated according to Formula 1.

[0046]

[0047] Where p is the sample spectrum vector; q is the reference standard spectrum vector; is the average spectrum; is the covariance; α p , α q is the standard deviation.

[0048] (3) The location of the “water absorption valley” on plant leaves and its reflectivity range

[0049] The leaves of camellia, camphor, heather, osmanthus, magnolia and other plants in Wuxi were cleaned and tested for visible light-near infrared reflectance spectra. The test results show that there are two "water absorption valleys" of plant leaves, which appear at 1450nm and 1930nm respectively, and the corresponding reflectance ranges are 10-30% and 4-10% respectively.

[0050] Example 1

[0051] A method for preparing a plant leaf imitation hydrogel composite material comprises the following steps:

[0052] (1) Preparation of green fabrics:

[0053] The colorant, printing auxiliary agent and water are uniformly mixed and stirred to a slurry to obtain a green printing paste, wherein the mass fractions of the components in the printing paste are respectively 0.6% of disperse blue NP-SBG, 0.28% of disperse dark blue HGL, 0.50% of disperse orange 30, 1.38% of dispersant 85A, 6% of thickener DM-5221G, and the rest is water, and the sum of the mass fractions of the above components is 100%. The printing paste is printed on the surface of the polyester fabric by flat screen printing, pre-dried at 80°C for 5 minutes, baked at 180°C for 2 minutes, reduced and cleaned at 80°C for 10 minutes, washed with water and dried at 80°C to obtain a green fabric.

[0054] (2) Preparation of hydrogel prepolymer solution:

[0055] 20 g of 1788 low-viscosity PVA was added to 80 g of water, stirred at 90° C. to completely dissolve and cooled to room temperature to obtain a PVA solution with a mass fraction of 20%; the PVA solution, hygroscopic monomer (2-acrylamide-2-methylpropane sulfonic acid), cross-linking agent (N,N-methylenebisacrylamide), initiator (ammonium persulfate) and water were mixed and stirred evenly, and nitrogen was purged for 20 minutes to prepare a hydrogel prepolymer solution, wherein the mass fractions of the components in the prepolymer solution were 60% of the PVA solution, 20% of the 2-acrylamide-2-methylpropane sulfonic acid (the mass ratio of PVA to 2-acrylamide-2-methylpropane sulfonic acid was 0.6:1), 0.7% of the N,N-methylenebisacrylamide, 0.6% of the ammonium persulfate, and the rest was water, and the sum of the mass fractions of the above components was 100%.

[0056] (3) Preparation of plant leaf-like hydrogel composites:

[0057] The green fabric obtained in step (1) was cut into a size of 10 cm*10 cm and spread flat in a mold, 15 mL of the hydrogel prepolymer solution obtained in step (2) was added, and polymerized at 60° C. for 12 h to obtain a plant leaf imitating hydrogel composite material.

[0058] The obtained bionic composite material was placed at 25°C and 60% RH for 24 hours for moisture absorption equilibrium, and then subjected to spectral testing to draw its spectral curve with that of Camellia japonica leaves ( Figure 2 ), the spectral correlation coefficient of the two was calculated according to Formula 1, and their reflectance at the two “water absorption valleys” was recorded (Table 1).

[0059] Depend on Figure 2 It can be seen that the spectral curve of the prepared bionic composite material is similar to that of Camellia japonica leaves, and the spectral correlation coefficient between the two is 0.984.

[0060] Example 2

[0061] A method for preparing a plant leaf imitation hydrogel composite material comprises the following steps:

[0062] (1) Preparation of green fabrics:

[0063] The colorant, printing auxiliary agent and water are uniformly mixed and stirred to a slurry to obtain a green printing paste, wherein the mass fractions of the components in the printing paste are respectively 0.6% of disperse blue NP-SBG, 0.28% of disperse dark blue HGL, 0.50% of disperse orange 30, 1.38% of dispersant 85A, 6% of thickener DM-5221G, 30% of binder DM 5128A, and the rest is water, and the sum of the mass fractions of the above components is 100%. The printing paste is printed on the surface of cotton fabric by flat screen printing, pre-dried at 80°C for 5 minutes, and baked at 180°C for 2 minutes to obtain a green fabric.

[0064] (2) Preparation of hydrogel prepolymer solution:

[0065] Same as step (2) in Example 1.

[0066] (3) Preparation of plant leaf-like hydrogel composites:

[0067] Same as step (3) in Example 1.

[0068] The obtained bionic composite material was placed under the conditions of 25° C. and 60% RH for 24 hours for moisture absorption equilibrium, and then a spectrum test was performed on it, and the spectrum correlation coefficient between it and the camellia leaf was calculated according to Formula 1.

[0069] After testing and calculation, the spectral correlation coefficient between the bionic composite material and camellia leaves is 0.981.

[0070] Example 3

[0071] A method for preparing a plant leaf imitation hydrogel composite material comprises the following steps:

[0072] (1) Preparation of green fabrics:

[0073] The colorant, printing auxiliary agent and water are uniformly mixed and stirred to a slurry to obtain a green printing paste, wherein the mass fractions of the components in the printing paste are 3% of chromium oxide, 2% of dispersant 85A, 6% of thickener DM-5221G, 30% of binder DM5128A, and the rest is water, and the sum of the mass fractions of the above components is 100%. The printing paste is printed on the surface of the polyester fabric by flat screen printing, and dried at 80°C to obtain the green fabric.

[0074] (2) Preparation of hydrogel prepolymer solution:

[0075] Same as step (2) in Example 1.

[0076] (3) Preparation of plant leaf-like hydrogel composites:

[0077] Same as step (3) in Example 1.

[0078] The obtained bionic composite material was placed under the conditions of 25° C. and 60% RH for 24 hours for moisture absorption equilibrium, and then a spectrum test was performed on it, and the spectrum correlation coefficient between it and the camellia leaf was calculated according to Formula 1.

[0079] After testing and calculation, the spectral correlation coefficient between the bionic composite material and camellia leaves is 0.977.

[0080] Example 4

[0081] The bionic composite material was prepared in the same manner as in Example 1, dried at 60° C., and then placed at 25° C. at 30%, 60%, and 90% RH for 24 hours for moisture absorption equilibrium.

[0082] The biomimetic composite materials with moisture absorption equilibrium at different humidity were subjected to spectral tests, and their reflectance at two “water absorption valleys” was recorded (Table 1).

[0083] Table 1 Reflectivity of the "water absorption valley" of the bionic composite material of Example 4 at different humidity

[0084]

[0085] As shown in Table 1, the plant leaf-mimicking hydrogel composite material prepared in Example 1 of the present invention can meet the spectral characteristic requirements of the "water absorption valley" of plant leaves at different humidity levels, and has a good simulation effect. And with the increase of humidity, the reflectivity of the bionic material in the "water absorption valley" gradually decreases, indicating that the material can adjust its water absorption as the humidity changes, and has good environmental adaptability.

[0086] Example 5

[0087] The bionic composite material was prepared in the same manner as in Example 1, cut into 6 cm*6 cm pieces and immersed in 250 mL of water for 6 h, then taken out and dried at 60° C., and placed at 25° C. and 60% RH for 24 h for moisture absorption equilibrium.

[0088] The obtained bionic composite material was subjected to spectral testing before and after immersion in water, and its reflectivity at two "water absorption valleys" was recorded (Table 2).

[0089] Comparative Example 1

[0090] A method for preparing a plant leaf imitation hydrogel composite material comprises the following steps:

[0091] (1) Preparation of green fabrics:

[0092] Same as step (1) in Example 1.

[0093] (2) Preparation of hydrogel prepolymer solution:

[0094] 20 g of 1788 low-viscosity PVA was added to 80 g of water, stirred at 90° C. to completely dissolve and cooled to room temperature to obtain a PVA solution with a mass fraction of 20%; the PVA solution, a cross-linking agent (N,N-methylenebisacrylamide), an initiator (ammonium persulfate) and water were mixed and stirred evenly, and nitrogen was purged for 20 minutes to prepare a hydrogel prepolymer solution, wherein the mass fractions of the components in the prepolymer solution were 80% of the PVA solution, 0.7% of the N,N-methylenebisacrylamide, 0.6% of the ammonium persulfate, and the rest was water, and the sum of the mass fractions of the above components was 100%.

[0095] (3) Preparation of plant leaf-like hydrogel composites:

[0096] Same as step (3) in Example 1.

[0097] The obtained bionic composite material was placed at 25°C and 60% RH for 24 hours for moisture absorption equilibrium, and then subjected to spectral testing to draw its spectral curve with that of Camellia japonica leaves ( Figure 2 ), and calculate the spectral correlation coefficient between the two according to Formula 1.

[0098] Depend on Figure 2It can be seen that the prepared biomimetic composite material has poor similarity with the spectral curve of Camellia japonica leaves, the spectral correlation coefficient between the two is 0.640, and there is no "water absorption valley" spectral feature. Comparative Example 1 shows that the hygroscopic monomer in the hydrogel has an important influence on the "water absorption valley" simulation effect of the biomimetic composite material.

[0099] Comparative Example 2

[0100] According to patent CN114214847A, the bionic material prepared by using hygroscopic metal salt includes the following steps:

[0101] (1) Preparation of green fabrics:

[0102] Same as step (1) in Example 1.

[0103] (2) Preparation of hydrogel prepolymer solution:

[0104] 1.0 g of sodium alginate powder was added into 100 mL of water, and the mixture was stirred until completely dissolved to obtain a sodium alginate aqueous solution; 10 g of calcium chloride was added into 90 g of water and mixed evenly to obtain a calcium chloride solution with a mass fraction of 10%.

[0105] (3) Preparation of bionic materials:

[0106] The green fabric obtained in step (1) is cut into a suitable size and placed in a mold, and the sodium alginate aqueous solution obtained in step (2) is added to make the thickness reach 3 mm, and then the calcium chloride solution obtained in step (2) is sprayed to make the thickness reach 6 mm. The green fabric is allowed to stand at room temperature for 30 minutes, and then dried at 50° C. for 24 hours to obtain a bionic material.

[0107] The bionic composite material prepared in step (3) was cut into 6 cm*6 cm pieces, immersed in 250 mL of water for 6 h, then taken out and dried at 60° C., and placed at 25° C. and 60% RH for 24 h for moisture absorption equilibrium.

[0108] The obtained bionic material was subjected to spectral testing before and after immersion in water, and its reflectivity at two "water absorption valleys" was recorded (Table 2).

[0109] Table 2 Reflectivity of the "water absorption valley" of the bionic materials prepared in Example 5 and Comparative Example 2 before and after immersion in water

[0110]

[0111] As can be seen from Table 2, the reflectivity of the bionic composite material prepared in Example 5 of the present invention before and after immersion in water has no obvious change, and has the characteristics of stable water absorption, good simulation effect and durability. However, the reflectivity of the bionic material prepared in Comparative Example 2 using hygroscopic metal salts is significantly improved after immersion in water, and the reflectivity at 1450nm is close to the upper limit of the "water absorption valley" of plant leaves, and the reflectivity at 1930nm can no longer meet the simulation requirements of plant leaves, indicating that the hygroscopic salt calcium chloride in the material has been lost in large quantities, and the simulation effect has deteriorated.

[0112] Comparative Example 3

[0113] (1) Preparation of green fabrics:

[0114] Same as step (1) in Example 1.

[0115] (2) Preparation of hydrogel prepolymer solution:

[0116] 20 g of 1788 low-viscosity PVA is added to 80 g of water, stirred at 90° C. to completely dissolve and cooled to room temperature to obtain a PVA solution with a mass fraction of 20%; the PVA solution, hygroscopic monomer, crosslinking agent, initiator and water are mixed and stirred evenly, and nitrogen is purged for 20 minutes to prepare a hydrogel prepolymer solution, wherein the mass fractions of the components in the prepolymer solution are respectively 40% of PVA solution, 40% of 2-acrylamide-2-methylpropane sulfonic acid (the mass ratio of PVA to 2-acrylamide-2-methylpropane sulfonic acid is 0.2:1), 0.7% of N,N-methylenebisacrylamide, 0.6% of ammonium persulfate, and the rest is water, and the sum of the mass fractions of the above components is 100%.

[0117] (3) Preparation of plant leaf-like hydrogel composites:

[0118] Same as step (3) in Example 1.

[0119] The obtained bionic composite material was placed under the conditions of 25°C and 60% RH for 24 hours for moisture absorption equilibrium, and then subjected to spectral testing. Its spectral correlation coefficient with that of Camellia japonica leaves was calculated according to Formula 1, and its reflectivity at two "moisture absorption valleys" was recorded.

[0120] After testing and calculation, the spectral correlation coefficient between the material and the camellia leaf is 0.713, and the reflectance of the spectral curve at 1450nm and 1930nm is 3.29% and 2.94% respectively. Compared with Example 1, when the amount of 2-acrylamide-2-methylpropanesulfonic acid is high, the hygroscopicity of the bionic material is enhanced, resulting in the reflectance of its reflection curve at 1450nm and 1930nm being too low, thereby failing to meet the spectral requirements of the "water absorption valley" of plant leaves.

[0121] Comparative Example 4

[0122] (1) Preparation of green fabrics:

[0123] Same as step (1) in Example 1.

[0124] (2) Preparation of hydrogel prepolymer solution:

[0125] 20 g of 1788 low-viscosity PVA is added to 80 g of water, stirred at 90° C. to completely dissolve and cooled to room temperature to obtain a PVA solution with a mass fraction of 20%; the PVA solution, hygroscopic monomer, crosslinking agent, initiator and water are mixed and stirred evenly, and nitrogen is purged for 20 minutes to prepare a hydrogel prepolymer solution, wherein the mass fractions of the components in the prepolymer solution are respectively 70% of the PVA solution, 10% of 2-acrylamide-2-methylpropane sulfonic acid (the mass ratio of PVA to 2-acrylamide-2-methylpropane sulfonic acid is 1.4:1), 0.7% of N,N-methylenebisacrylamide, 0.6% of ammonium persulfate, and the rest is water, and the sum of the mass fractions of the above components is 100%.

[0126] (3) Preparation of plant leaf-like hydrogel composites:

[0127] Same as step (3) in Example 1.

[0128] The obtained bionic composite material was placed under the conditions of 25°C and 60% RH for 24 hours for moisture absorption equilibrium, and then subjected to spectral testing. Its spectral correlation coefficient with that of Camellia japonica leaves was calculated according to Formula 1, and its reflectivity at two "moisture absorption valleys" was recorded.

[0129] After testing and calculation, the spectral correlation coefficient between the material and Camellia japonica leaves is 0.811, and the reflectance of its spectral curve at 1450nm and 1930nm is 43.39% and 14.33% respectively. Compared with comparative example 1, after adding 2-acrylamide-2-methylpropane sulfonic acid, the bionic material has a certain hygroscopicity, and the spectral curve shows two "water absorption valley" characteristics. Compared with Example 1, the amount of 2-acrylamide-2-methylpropane sulfonic acid added is less, and the reflectance of the bionic material reflection curve at 1450nm and 1930nm is high, so it cannot meet the spectral requirements of the "water absorption valley" of plant leaves.

[0130] Comparative Example 5

[0131] (1) Preparation of green fabrics:

[0132] Same as step (1) in Example 1.

[0133] (2) Preparation of hydrogel prepolymer solution:

[0134] 20 g of 1788 low-viscosity PVA was added to 80 g of water, stirred at 90° C. to completely dissolve and cooled to room temperature to obtain a PVA solution with a mass fraction of 20%; the PVA solution, hygroscopic monomer (acrylamide), cross-linking agent (N,N-methylenebisacrylamide), initiator (ammonium persulfate) and water were mixed and stirred evenly, and nitrogen was purged for 20 minutes to prepare a hydrogel prepolymer solution, wherein the mass fractions of the components in the prepolymer solution were 60% of the PVA solution, 20% of acrylamide, 0.7% of N,N-methylenebisacrylamide, 0.6% of ammonium persulfate, and the rest was water, and the sum of the mass fractions of the above components was 100%.

[0135] (3) Preparation of plant leaf-like hydrogel composites:

[0136] Same as step (3) in Example 1.

[0137] The obtained bionic composite material was placed under the conditions of 25°C and 60% RH for 24 hours for moisture absorption equilibrium, and then subjected to spectral testing. Its spectral correlation coefficient with that of Camellia japonica leaves was calculated according to Formula 1, and its reflectivity at two "moisture absorption valleys" was recorded.

[0138] After testing and calculation, the spectral correlation coefficient between the material and the camellia leaf is 0.827, and the reflectance of its spectral curve at 1450nm and 1930nm is 25.46% and 12.08% respectively. Compared with Example 1, the spectral correlation coefficient between the material and the camellia leaf is reduced, and the reflectance at 1930nm exceeds the spectral requirement of the "water absorption valley" of plant leaves.

[0139] Comparative Example 6

[0140] (1) Preparation of green fabrics:

[0141] Same as step (1) in Example 1.

[0142] (2) Preparation of hydrogel prepolymer solution:

[0143] 20g of acrylic acid is added into 80g of water and stirred to obtain an acrylic acid solution with a mass fraction of 20%; the acrylic acid solution, a hygroscopic monomer, a crosslinking agent, an initiator and water are mixed and stirred evenly, and nitrogen is purged for 20 minutes to prepare a hydrogel prepolymer solution, wherein the mass fractions of the components in the prepolymer solution are 60% of the acrylic acid solution, 20% of 2-acrylamide-2-methylpropanesulfonic acid, 0.7% of N,N-methylenebisacrylamide, 0.6% of ammonium persulfate, and the rest is water, and the sum of the mass fractions of the above components is 100%.

[0144] (3) Preparation of plant leaf-like hydrogel composites:

[0145] Same as step (3) in Example 1.

[0146] The obtained bionic composite material was placed under the conditions of 25°C and 60% RH for 24 hours for moisture absorption equilibrium, and then subjected to spectral testing. Its spectral correlation coefficient with that of Camellia japonica leaves was calculated according to Formula 1, and its reflectivity at two "moisture absorption valleys" was recorded.

[0147] After testing and calculation, the spectral correlation coefficient between the material and the camellia leaf is 0.755, and the reflectance of its spectral curve at 1450nm and 1930nm is 8.11% and 3.02% respectively. Compared with Example 1, the spectral correlation coefficient between the material and the camellia leaf is reduced, and the reflectance at 1450nm and 1930nm is too low, which does not meet the spectral requirements of the "water absorption valley" of plant leaves.

[0148] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a plant leaf-mimicking hydrogel composite material, characterized in that: The steps include: (1) Preparation of green fabrics: The colorant, printing auxiliary agent and water are mixed evenly and stirred into a slurry to obtain a green printing paste; then the printing paste is printed on the surface of the fabric by a screen printing method to obtain a green fabric; (2) Preparation of hydrogel prepolymer solution: PVA, a strong hygroscopic monomer, a cross-linking agent, an initiator, and water are mixed and stirred uniformly to obtain a hydrogel prepolymer solution; (3) Preparation of plant leaf-like hydrogel composites: The green fabric obtained in step (1) is mixed with the hydrogel prepolymer solution obtained in step (2), and the mixture is heated and polymerized to obtain a plant leaf imitating hydrogel composite material.

2. The method according to claim 1, characterized in that The colorant described in step (1) includes one or more of chromium oxide, disperse dyes, vat dyes, acid dyes, reactive dyes, dry leaf powder, and sodium copper chlorophyll.

3. The method according to claim 1, characterized in that The printing auxiliary agent described in step (1) includes one or more of a dispersant, a thickener, and a binder.

4. The method according to claim 3, characterized in that The dispersant includes one or more of 85A, AD-4600, 5080W, NNO, DM 1501, DM 1501N, PVP, and BYK-190.

5. The method according to claim 3, characterized in that: The thickener includes one or more of TF-3181SS, TF-313E, TF-313B, TF-312NW, DM-5221G, DM-5228, DM-5298, and sodium alginate.

6. The method according to claim 3, characterized in that The adhesive includes one or more of TF-3211, TF-321A, TF-3201YD, TF-3201R, TEP, BST-N788, DM 5128A, and DM 5120.

7. The method according to claim 1, characterized in that The fabric described in step (1) includes one or more of polyester fabric, polyester-cotton blended fabric, cotton fabric, viscose fabric, and nylon fabric.

8. The method according to claim 1, characterized in that The green printing paste described in step (1) is prepared by mixing a colorant, a printing auxiliary agent and water and stirring them uniformly into a slurry; wherein the amount of the colorant in the green printing paste is 0.1-5.0wt%; the amount of the printing auxiliary agent in the green printing paste is 5-40.0wt%.

9. The method according to claim 1, characterized in that: The highly hygroscopic monomer described in step (2) includes one or more of acrylic acid, acrylic acid salts, acrylamide, acrylic acid-acrylamide copolymer, N-isopropylacrylamide, 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer, sodium p-styrene sulfonate, lignin, chitosan, cellulose, carboxymethyl cellulose, sodium alginate, and quaternary ammonium salt guar gum.

10. The method according to claim 1, characterized in that In step (2), the mass fraction of PVA in the hydrogel prepolymer solution is 10%-20%, and the mass fraction of the strong hygroscopic monomer is 0-50%.

11. The method according to claim 1, characterized in that: In step (2), the mass ratio of PVA to the highly hygroscopic monomer in the hydrogel prepolymer solution is (0.4-0.8):

1.

12. The method according to any one of claims 1 to 11, characterized in that: In step (2), the cross-linking agent includes one or more of N,N-methylenebisacrylamide, glutaraldehyde, citric acid, and ethylene glycol diacrylate.

13. The method according to any one of claims 1 to 11, characterized in that: In step (2), the mass fraction of the crosslinking agent in the hydrogel prepolymer solution is 0.1-1.0%.

14. The method according to any one of claims 1 to 11, characterized in that: In step (2), the initiator includes one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, epichlorohydrin, and boric acid.

15. The method according to any one of claims 1 to 11, characterized in that: In step (2), the mass fraction of the initiator in the hydrogel prepolymer solution is 0.1-1.0%.

16. A plant leaf imitation hydrogel composite material prepared by the method according to any one of claims 1 to 15.

17. Application of the plant leaf imitating hydrogel composite material according to claim 16 in the field of national defense and security.

Citation Information

Patent Citations

  • Visible light-near infrared bionic spectrum simulation material containing water-absorbable transparent coating and preparation method of visible light-near infrared bionic spectrum simulation material

    CN114214847A

  • Hyperspectral stealth biomimetic material and application thereof

    CN114485272A

  • Visible light-near infrared spectrum simulation bionic blade and preparation method thereof

    CN116029125A

  • Hyperspectral biomimetic thin film material for simulating green vegetation leaves and preparation method of hyperspectral biomimetic thin film material

    CN117106273A

Cited By

  • High-air-permeability imitated green leaf material and preparation method thereof

    CN121344870A

  • Leaf-like hydrogel composite fabric and preparation method thereof

    CN122103680A

  • A leaf-like hydrogel composite fabric and a preparation method thereof

    CN122103680B

  • Hydrogel composite material imitating plant leaves, and preparation method therefor

    WO2026086132A1